ANALISIS NILAI TAMBAH AGROINDUSTRI KRIPIK UBI DI KOTA PONTIANAK (Jurnal Social Economic of Agriculture, 2015)
Agro processing cassava chips businesses is one of the efforts that are currently being developed in the city of Pontianak. The existence of this business is expected to improve the quality,  profitability,  value-added products. The purpose of this study was to determine the magnitude of the added value obtained from cassava chips processing in Pontianak. This research was conducted using descriptive methods, population in this study were cassava chips entrepreneurs in the city of Pontianak. Data collected included primary data and secondary data. Techniques of data collection is done by direct interviews with respondents and recording data from relevant agencies. Data analysis was performed by using a format according to the analysis of value-added Hayami method. The results of the study  show that the value added obtained in cassava chips agro-businesses in the city of Pontianak is Rp. 25 231 per kg or by 78.8%, with gains amounting to Rp. 24269.8 / kg with a profit margin of 95.56% employer.